Students’ Misconceptions in Chemistry Learning: A Systematic Literature Review from 2015 to 2025 - Pahriah, Pahriah; Sudatha, I Gde Wawan; Suartama, I Kadek; Santosa, Made Hery (Universitas Pendidikan Mandalika, 2025)
This study aims to identify the forms of misconceptions in chemistry learning, the methods/instruments used to detect these misconceptions, and effective instructional strategies to address them through a Systematic Literature Review (SLR) approach. The review was conducted on 24 scientific articles published between 2015 and 2025, obtained from the Scopus and Google Scholar databases (via Publish or Perish). Article selection was carried out in stages following the PRISMA flow, and the results were analyzed using a thematic content analysis approach. The review findings indicate that the topics most frequently associated with misconceptions are chemical bonding, acid-base concepts, chemical equilibrium, and reaction rates. The most commonly used instruments to identify misconceptions are three-tier diagnostic tests, followed by interviews and two-tier tests. Effective instructional strategies include the use of multiple representations, digital simulations, the 5E model, inquiry-based learning, and educational games. The study also revealed several research gaps, such as the lack of longitudinal studies, limited topic coverage in chemistry, and the underutilization of interactive digital technologies. Therefore, the development of innovative learning approaches and technology-based conceptual assessments is necessary to sustainably reduce misconceptions in chemistry learning.